Metabolic Responses to Exercise Across Different Age Groups: A Literature Review - Simatupang, Ayman Faiz; Saragi, Muhammad Ridoh; Pinem, Hadsen Daris; Manalu, Nimrot (Journal Coaching Education Sports, 2025)
Physical activity plays a vital role in maintaining metabolic health and preventing various chronic diseases such as obesity, type 2 diabetes, and cardiovascular disease. Metabolic responses to exercise vary across different age groups, influenced by physiological changes such as decreased muscle mass, insulin sensitivity, and aerobic capacity. This study uses a systematic literature review method by examining studies discussing metabolic changes during and after exercise in various age groups. Searches were conducted through databases including PubMed, ScienceDirect, Google Scholar, and Consensus using keywords such as metabolic response to exercise, age-related metabolic adaptations, and exercise and metabolism across lifespan. The studies analyzed included metabolic measurements such as oxygen consumption (VO₂), energy expenditure, insulin sensitivity, and fat and carbohydrate metabolism. The review showed that younger individuals generally have higher metabolic efficiency compared to older adults, although exercise benefits all age groups. Energy expenditure increases with exercise intensity, but no significant differences were observed across age groups during low to moderate intensity exercise. High-intensity interval training (HIIT) significantly increased fat oxidation in middle-aged adults. Additionally, older sedentary individuals exhibited higher postprandial triglyceride levels than younger or more active individuals. The timing of exercise also influenced metabolic responses: morning exercise was more effective in enhancing lipid metabolism, while afternoon workouts were more optimal for improving insulin sensitivity.